Therapeutic effect of oxiracetam combined with Ginkgo biloba extract on acute cerebral hemorrhage and its effect on serum inflammatory factors - Jin⁃hai MA; Tao WANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2019)
Objective To investigate the efficacy and safety of oxiracetam combined with Ginkgo biloba leaf extract in the treatment of acute cerebral hemorrhage and the effect of oxiracetam on the expression of serum inflammatory factors. Methods A total of 210 cases of acute cerebral hemorrhage diagnosed definitely from June 2016 to January 2018 were included. Patients were divided into two groups by randomized block design method: simple oxiracetam treatment group (oxiracetam treatment group) and oxiracetam combined with Ginkgo biloba leaf extract treatment group (combined treatment group). The curative effect of the two treatment schemes were evaluated, and quantitative analysis was made on the changes of brain edema and cerebral hematoma. National Institutes of Health Stroke Scale (NIHSS), Montreal Cognitive Rating Scale (MoCA), and Activity of Daily Living Capacity Scale (ADL) were used to evaluate neurological function, cognitive function, and activities of daily living of patients. The changes of oxidative stress index and serum inflammatory factor expression before and after treatment were monitored, and adverse drug reactions were recorded. Results After treatment with the two regimens, brain edema and hematoma were decreased (all P =0.000), NIHSS score was decreased, MoCA and ADL score were increased (all P =0.000), superoxide dismutase (SOD) level was increased, malondialdehyde (MDA) and nitric oxide(NO)level were decreased(all P=0.000),serum inflammatory factors interleukin-8 (IL-8) and intercellular adhesion molecular-1 (ICAM-1) level were decreased, and B-type natriuretic peptide (BNP)level was increased (all P=0.000). The total effective rate of the combined treatment group was higher than that of the oxiracetam treatment group [92.38%(97/105)vs.80.95%(85/105);χ2=5.934, P=0.015]. The incidence of adverse drug reactions of the combined treatment group was lower than that of the oxiracetam treatment group [8.57% (9/105) vs. 19.05% (20/105); χ2 =4.841, P =0.028]. Conclusions Oxiracetam combined with Ginkgo biloba leaf extract can effectively reduce the amount of brain edema and cerebral hemorrhage in patients with acute cerebral hemorrhage, thereby improving nerve function, cognitive function and activities of daily living. It has good efficacy and safety. Therefore,it is valuable for clinical application.